РАЗВИТИЕ МОНУМЕНТАЛЬНОЙ СКУЛЬПТУРЫ В УЗБЕКИСТАНЕ - Кодирова Зилола Рузибоевна (Journal Park Publishing, 2025)
This study analyzes the evolution of monumental sculpture in Uzbekistan, viewing it as a key indicator of sociocultural and ideological transformations. The paper traces three main stages of development: the Soviet period, characterized by the dominance of socialist realism and ideological propaganda; the early post-Soviet period (1991–early 2000s), marked by de-Sovietization and the active construction of a new national pantheon of heroes, headed by Amir Temur; and the modern period, characterized by the diversification of subject matter and the search for new forms of expressing national identity. The methodological basis of the study includes historical, chronological, art historical, and semiotic analysis of iconic monumental objects. The results demonstrate that monumental sculpture has served and continues to serve as a powerful instrument of state policy in the field of shaping historical memory and national ideology.
Keywords: Monumental sculpture, Uzbekistan, national identity, Soviet legacy, Amir Temur, post-Soviet art, urban space, politics of memory.